2018
DOI: 10.1016/j.ejvs.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

International Consortium of Vascular Registries Consensus Recommendations for Peripheral Revascularisation Registry Data Collection

Abstract: A modified Delphi study allowed 25 international vascular registry experts to achieve a consensus recommendation for a minimum core data set and an optimum data set for peripheral arterial revascularisation registries. Continued global harmonisation of registry infrastructure and definition of items will overcome limitations related to single country investigations and enhance the development of real world evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 17 publications
(4 reference statements)
0
43
0
3
Order By: Relevance
“…One way of improving registry data collection is to reach consensus through a Delphi process, and two such processes took place in 2018. The first paper identified 79 recommended variables to be included in registries on all patients with PAD, 251 including obvious variables such as survival and amputation. The second Delphi process focused on ALI: 23 variables were recommended for the minimum core data…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…One way of improving registry data collection is to reach consensus through a Delphi process, and two such processes took place in 2018. The first paper identified 79 recommended variables to be included in registries on all patients with PAD, 251 including obvious variables such as survival and amputation. The second Delphi process focused on ALI: 23 variables were recommended for the minimum core data…”
Section: 12mentioning
confidence: 99%
“…C Behrendt et al (2019),252 Behrendt et al (2018)249,251 stent graft thrombosis. The EVAR-I trial reported a 3 e 4 times higher rate of graft related complications after endovascular aneurysm repair compared with open aortic surgery 260.…”
mentioning
confidence: 99%
“…In the prospectively collected registry data (R), we have a pre-defined set of p variables which were consented before [10,22] and have q variables in the health insurance claims data (C), whereas we can transform information in variables as International Classification of Diseases (ICD) coding in several dummy variables (e. g. diabetes yes/no). We have a set of m variables which are present in both data sets m < p,q, (intersection variables e. g. age, gender, diabetes, death etc.).…”
Section: Group Wise Linking and Comparison For Internal Validitymentioning
confidence: 99%
“…The Vascunet has therefore put a significant effort into creating minimum datasets for common vascular surgical procedures in carotid artery disease, aortic surgery and PAD interventions. The recommendations for peripheral revascularization registry data collection were recently created by a modified Delphi approach with on-line interaction within 14 countries among international vascular surgeons and registry mem-bers of the ICVR [19]. The Vascunet and ICVR have additionally performed international benchmarking studies of vascular surgical practice and outcome, identifying important variations in the practice of vascular surgery between countries and regions [20][21][22][23].…”
Section: International Registry Collaborationmentioning
confidence: 99%